PEMBANGUNAN APLIKASI HASIL BRIEFING PADA THE HILLS HOTEL BATAM - Halim, Roy Dwi Putra; Simalango, Holong Marisi (Journal of Digital Ecosystem for Natural Sustainability, 2021)
Operational activities in hotels are the most important thing in the hospitality business because they are closely related to service. Errors and deficiencies on the operational side can directly affect service to guests. The delivery of operational activities between departments at the time of the briefing must be clear so that there is no miscommunication between departments. Submission of the report on the results of the briefing via email that difficulties were found and even were not conveyed properly. The fact of this finding is because some employees only open emails via computers because the report results are in the form of .xlsx files and there are still many incoming emails that result in unanswered information on the results of the briefing. The research method used is observation, interviews, and literature study. The software method used in software development is to use the waterfall model. This application development uses Visual Studio Code and uses MySQL as a database management system. The final result of this research is to resolve the findings of ongoing problems by building a reporting application and reminder from the results of mobile-based briefings that can be used anywhere and anytime. Reporting all archives that are neatly organized can improve operational activities at The Hills Hotel Batam without any miscommunication between department heads.